2004
DOI: 10.1111/j.1365-2249.2004.02594.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical induction of HO-1 suppresses lupus nephritis by reducing localiNOS expression and synthesis of anti-dsDNA antibody

Abstract: SUMMARYThere is accumulating evidence that haem oxygenase (HO)-1 plays a protective role in various disorders. The beneficial efficacy of HO-1 induction therapy has been shown in renal diseases such as glomerulonephritis, interstitial nephritis and drug induced nephrotoxicity. However, involvement of HO-1 in the development of autoimmune renal diseases remains uncertain. To assess the clinical efficacy of HO-1 induction therapy for lupus glomerulonephritis, MRL/ lpr mice were intraperitoneally injected with 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 46 publications
4
50
0
Order By: Relevance
“…3956 RUEDA ET AL several autoimmune disorders such as RA, inflammatory bowel disease, systemic lupus erythematosus, and multiple sclerosis (7,8,11,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3956 RUEDA ET AL several autoimmune disorders such as RA, inflammatory bowel disease, systemic lupus erythematosus, and multiple sclerosis (7,8,11,22).…”
Section: Discussionmentioning
confidence: 99%
“…All the activities mentioned above suggest that HO-1 is a protective molecule. In fact, HO-1 induction shows beneficial effects in cardiovascular disease, transplantation, acute inflammation, and autoimmune disorders (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Examples include NADPH oxidases, which are heme enzymes (Sumimoto 2008). The induction and absence of HO-1 have been shown to modify the immune system (Woo et al 1998;Kapturczak et al 2004;Takeda et al 2004;Chauveau et al 2005;McDaid et al 2005;Matsushima et al 2009;Tzima et al 2009;Schumacher et al 2012;So et al 2012). However, the mechanisms underlying the HO-1-mediated modulation of the immune system remain elusive (Soares et al 2009).…”
Section: Bach2 and Bach1 Orchestrate Immunitymentioning
confidence: 99%
“…These cytoprotective functions can be applied for therapeutic purposes. We previously reported that chemical induction of HO-1 suppresses lupus nephritis (15) and that adenovirus vector-mediated gene transfer of HO-1 complementary DNA (cDNA) has beneficial effects on lipopolysaccharide (LPS)-induced lung injury (16), influenza viral pneumonia (17), bleomycin-induced pulmonary fibrosis (18), Pseudomonas chronic respiratory infection (19), and elastase-induced emphysema (20) in mouse models. Similarly, favorable outcomes have been achieved with therapies using HO-1 chemical inducers or with gene transfer in other animal models, including ischemia/ reperfusion-induced injuries of the heart (9) and liver (21), LPS-induced ocular inflammation (22), and allogenic heart allotransplantation (23).…”
mentioning
confidence: 99%